Analisis Minimalisasi Biaya Antibiotik Ceftriaxone dan Cefotaxime pada Pasien Pneumonia Dewasa Rawat Inap RSUDP NTB 2018 - Aulia Nabila; Candra Eka Puspitasari; G.A.P Sri Erwinayanti (Jurnal Sains dan Kesehatan, 2021)
Pneumonia is an infection on the lung tissue that caused the lung would not be able to work properly. The first-line choice of therapy in pneumonia is using cephalosporin class of antibiotic which are ceftriaxone and cefotaxime. Both of those therapies have significant difference in cost, so that a pharmaceconomic analysis needs to be done using the cost-minimization analysis (CMA) method. This research to analyze minimization cost of antibiotic ceftriaxone and cefotaxime in adult pneumonia patients with cured outcomes in inpatients at RSUD Provinsi NTB in 2018. The research was conducted from July to August 2019. The sampling technique in this research was total sampling with 18 samples. The data used is retrospective in 2018. Ceftriaxone and cefotaxime cost-minimization analysis using comparison of the total cost calculation showed that cefotaxime therapy is more cost-minimized Rp 1.297.829 or 26,1% than ceftriaxone therapy. There was a significant difference between hospitalization cost and drug cost for the ceftriaxone and cefotaxime drug groups using the t-Test with p < 0.05. Keywords : pneumonia, ceftriaxone, cefotaxime, cost-minimization analysis